ChemInform Abstract: The Oxidation of Alcohols with O‐Iodoxybenzoic Acid (IBX) in Aqueous Nanomicelles at Room Temperature. Issue 43 (21st October 2014) - Xie, Aming; Zhou, Xiangxiang; Feng, Liandong; Hu, Xinyu; Dong, Wei
Abstract A nonionic amphiphilic surfactant is prepared and applied as effective micelle forming species to promote the oxidation of primary and secondary alcohols with IBX in water.